CEB-FIP model code 1990 design code (Thomas Telford, 1993)
This document is a comprehensive design code for concrete. It is the result of a comprehensive revision to the original model code of 1978, which was produced jointly by the Comit Euro-International du Beton (CEB) and the Federation International de la Precontrainte (FIP).